2013
DOI: 10.1016/j.mce.2012.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol, acting through estrogen receptor alpha, restores dimethylarginine dimethylaminohydrolase activity and nitric oxide production in oxLDL-treated human arterial endothelial cells

Abstract: a b s t r a c tAsymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide (NO) synthase. ADMA accumulation, mainly due to a decreased dimethylarginine dimethylaminohydrolase (DDAH) activity, has been related to the development of cardiovascular diseases. We investigate whether estradiol prevents the changes induced by oxidized low density lipoprotein (oxLDL) on the DDAH/ADMA/NO pathway in human umbilical artery endothelial cells (HUAEC). HUAEC were exposed to estradiol, native LDL (nLDL), ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…Our group has previously described that the oxidation state of LDL has a differential regulatory effect in several mechanisms that are of importance for the development of atherosclerosis [12]. To test whether Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously described that the oxidation state of LDL has a differential regulatory effect in several mechanisms that are of importance for the development of atherosclerosis [12]. To test whether Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human umbilical artery endothelial cells (HUAECs) were isolated from arteries of human umbilical cords, as previously described [12]. Briefly, umbilical arteries were isolated, cannulated, washed with PBS and incubated for 15 min with 0.2% collagenase type II.…”
Section: Endothelial Cell Culture and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from other laboratories and ours have repeatedly demonstrated suggests that DDAH/ADMA pathway plays a key role in regulation of vascular endothelial functions under physiological and pathological conditions. 8,9,22,23 As an endogenous inhibitor of NOS, ADMA is emerging as a biomarker for endothelial dysfunction. 24 In this study, we have found that the plasma levels of ADMA were significantly elevated in the hyperlipidemic rats concomitant with endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…7 Accumulating evidence has demonstrated that the elevated plasma levels of ADMA in many cardiovascular diseases including hyperlipidemia are due to, at least partially, the decrease in DDAH activity. [8][9][10][11] Although the activities of DDAH have been reported to be reduced in hyperlipidemic animals, it is not known whether the decrease in DDAH activities involves the suppression of DDAH gene expression.…”
Section: Introductionmentioning
confidence: 99%